The Relationship Of Knowledge Management And Digital Maturity Towards Talent Resilience Of Kurnia Bumi Raya (KBR) Management In Using The Lark Application - Permana, Arie Soleh; Zuhriatusobah H.S, Juju; Aisah; Komalasari, Ela (Jurnal Bisnis dan Ekonomi, 2024)
His research aims to analyze the influence of knowledge management and digital maturity on resilience in KBR Management talent. This research uses quantitative research methods with a sample size of 30 people who are all the talents of KBR Management. The research results show that partially there is no influence between knowledge management and resilience. This shows that an individual's ability to adapt is not influenced by knowledge management. There is a significant positive influence between digital maturity and resilience. This shows that the better the level of digital maturity, the easier it is for individuals to adapt. Simultaneously there is a positive and significant influence between knowledge management and digital maturity on resilience. This means that the better the level of knowledge management and digital maturity in the KBR talent, the better the level of adaptability or resilience in using the Lark application.Kata Kunci : Knowledge Management, Digital Maturity dan Resiliansi